Overexpression of pea α‐carboxyltransferase in Arabidopsis and camelina increases fatty acid synthesis leading to improved seed oil content. (27th March 2022) - Wang, Minmin; Garneau, Matthew G.; Poudel, Arati N.; Lamm, Daniel; Koo, Abraham J.; Bates, Philip D.; Thelen, Jay J.
Significance Statement: The limiting subunit of plant acetyl‐CoA carboxylase was identified as α‐carboxyltransferase via absolute protein quantification; overexpression of this subunit in Arabidopsis and Camelina led to an increase of both fatty acid synthesis rate and seed oil content. SUMMARY: Heteromeric acetyl‐CoA carboxylase (htACCase) catalyzes the committed step of de novo fatty acid biosynthesis in most plant plastids. Plant htACCase is comprised of four subunits: α‐ and β‐carboxyltransferase (α‐ and β‐CT), biotin carboxylase, and biotin carboxyl carrier protein. Based on in vivo absolute quantification of htACCase subunits, α‐CT is 3‐ to 10‐fold less abundant than its partner subunit β‐CT in developing Arabidopsis seeds [Wilson and Thelen, J. Proteome Res., 2018, 17 (5)]. To test the hypothesis that low expression of α‐CT limits htACCase activity and flux through fatty acid synthesis in planta, we overexpressed Pisum sativum α‐CT, either with or without its C‐terminal non‐catalytic domain, in both Arabidopsis thaliana and Camelina sativa. First‐generation Arabidopsis seed of 35S::Ps α‐CT ( n  = 25) and 35S::Ps α‐CT Δ406‐875 ( n  = 47) were on average 14% higher in oil content (% dry weight) than wild type co‐cultivated in a growth chamber. First‐generation camelina seed showed an average 8% increase compared to co‐cultivated wild type. Biochemical analyses confirmed the accumulation of Ps α‐CT and Ps α‐CT Δ406‐875 protein and higher htACCase activity in overexpression lines during early seed development. Overexpressed Ps α‐CT co‐migrated with native At β‐CT during anion exchange chromatography, indicating co‐association. By successfully increasing seed oil content upon heterologous overexpression of α‐CT, we demonstrate how absolute quantitation of in vivo protein complex stoichiometry can be used to guide rational metabolic engineering.